Teaching Reading Comprehension Using Jigsaw Technique to Eight Grade Students at SMP Negeri 16 - Nur Fajria; Nadrun Nadrun; Mashuri Mashuri; Anjar Kusuma Dewi (Hasanuddin University, 2025)
This study examines the effectiveness of the Jigsaw technique in improving reading comprehension among eighth-grade students at SMP Negeri 16 Palu. Reading comprehension is essential for academic success, yet many students struggle due to low motivation, limited vocabulary, and anxiety when reading English texts. To address these issues, a quasi-experimental design was used involving an experimental group taught with the Jigsaw technique and a control group taught using conventional methods. Both groups completed pre-tests and post-tests to assess their reading comprehension before and after the intervention. The results showed a significant improvement in the experimental group’s reading comprehension scores compared to the control group. The mean post-test score for the experimental group was 82.47, while the control group scored 61.10, indicating a notable positive impact of the Jigsaw technique. Statistical analysis confirmed this difference was significant at the 0.05 level. The Jigsaw technique fostered cooperative learning by increasing student engagement and encouraging active participation. Group discussions allowed students to share interpretations and collaboratively analyze texts, which enhanced their ability to identify main ideas, supporting details, and text structures. Additionally, role division and repeated group interactions improved information recall and retention. In conclusion, the Jigsaw technique is an effective instructional strategy for enhancing students’ reading comprehension, especially at the literal level. These findings support incorporating cooperative learning methods in English teaching to help students overcome common reading comprehension difficulties.